Description of a New Argasid Tick (Acari: Ixodida) from Bat Caves in Brazilian Amazon - Nava, Santiago (2010)
Nothoaspis amazoniensis n. sp. (Acari: Ixodida: Argasidae) is described from adult and immature ticks (nymph II, nymphI, larva) collected from bat caves in the Brazilian Amazon. Also, 16S rDNA sequences are provided. The diagnostic characters foradults are the presence of false shield or nothoaspis, an anteriorly projecting hood covering the capitulum, a medial extension of palpalarticle I (flaps), genital plate extending from coxa I to IV, absence of 2 setae on the internal margin of the flaps, a minute hypostomewithout denticles, presence of a central pore in the base of hypostome, and a reticulate surface pattern on the posterior half of thenothoaspis in males. The nymph II stage is characterized by a hood that is small in relation to the capitulum, short coxal setae, palpalflaps lacking setae on the internal margin, long hypostome, pointed with dentition 4/4 apically, and the anterior half of the body iscovered by a cell-like configuration. Nymph I stage is characterized by a hood, small in relation to the capitulum, dorsum of the bodycovered by a cell-like configuration, venter integument covered by a cell-like configuration, and hypostome dentition 4/4 with apicesthat are ‘‘V’’-shaped. Diagnostic characters of the larvae are the number and size of dorsal setae, and the shape of scutum andhypostome. The new species appears to have a life cycle with a larva that feeds on bats, a non-feeding nymphal stage (nymph I), afeeding nymphal stage (nymph II), and adults that probably represent non-feeding stages.